Effects of muscle - tendon length on joint moment and power during sprint starts - Mero, A.; Kuitunen, S.; Harland, M.; Kyröläinen, H.; Komi, P. V. (Journal of Sports Sciences, 2006)
The aim of this study was to examine the effects of muscle - tendon length on joint moment and power during maximal sprint starts. Nine male sprinters performed maximal sprint starts from the blocks that were adjusted either to 40° or 65° to the horizontal. Ground reaction forces were recorded at 833 Hz using a force platform and kinematic data were recorded at 200 Hz with a film camera. Joint moments and powers were analysed using kinematic and kinetic data. Muscle - tendon lengths of the medial gastrocnemius, soleus, vastus medialis, rectus femoris and biceps femoris were calculated from the set position to the end of the first single leg contact. The results indicated that block velocity (the horizontal velocity of centre of mass at the end of the block phase) was greater (P < 0.01) in the 40° than in the 65° block angle condition (3.39 ± 0.23 vs. 3.30 ± 0.21 m · s-1). Similarly, the initial lengths of the gastrocnemius and soleus of the front leg in the block at the beginning of force production until half way through the block phase were longer (P < 0.001) in the 40° than in the 65° block angle condition. The initial length and the length in the middle of the block phase were also longer in the 40° than in the 65° block angle condition both for both the gastrocnemius (P < 0.01) and soleus (P < 0.01 - 0.05) of the rear leg. In contrast, the initial lengths of the rectus femoris and vastus medialis of the front leg were longer (P < 0.05) in the 65° than in the 40° block angle condition. All differences gradually disappeared during the later block phase. The peak ankle joint moment (P < 0.01) and power (P < 0.05) during the block phase were greater in the 40° than in the 65° block angle condition for the rear leg. The peak ankle joint moment during the block phase was greater (P < 0.05) in the 40° block angle for the front leg, whereas the peak knee joint moment of the rear leg was greater (P < 0.01) in the 65° block angle condition. The results suggest that the longer initial muscle - tendon lengths of the gastrocnemius and soleus in the block phase at the beginning of force production contribute to the greater peak ankle joint moment and power and consequently the greater block velocity during the sprint start.